Nuclear Calcium signaling - Bengtson, C. Peter; Bading, Hilmar (Synaptic Plasticity, 2012)
Calcium is the major intracellular messenger linking synaptic activity in neurons to gene expression to control diverse functions including adaptive responses to synaptic activity as well as survival and death (Bading et al. 1993; Hardingham et al. 1997; Chawla and Bading 2001; West et al. 2001; Zhang et al. 2007; Flavell and Greenberg 2008; Mellstrom et al. 2008; Redmond 2008; Wayman et al. 2008; Bootman et al. 2009; Zhang et al. 2009; Hardingham and Bading 2010). Calcium entry at the synapse acts locally to activate signaling cascades which regulate posttranslational modifications essential for synaptic plasticity, such as the insertion of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) into the postsynaptic membrane (Soderling 2000; Malinow and Malenka 2002; Ehrlich and Malinow 2004). Synaptic activity can also evoke calcium signals in the nucleus which regulate gene pools largely through the phosphorylation of cAMP response element-binding protein (CREB) and its coactivator, CREB-binding protein (CBP) (Bading et al. 1993; Hardingham et al. 1997; Hardingham et al. 1999; Hu et al. 1999; Hardingham et al. 2001b; Impey et al. 2002; Zhang et al. 2009). Distinct mechanisms have been proposed to mediate synaptically generated calcium signals in subcompartments of pyramidal neurons; N-methyl-d-aspartate receptors (NMDARs) and ryanodine receptors have been implicated in the spine, inositol 3,4,5 triphosphate (IP3) receptors in the dendrites, and L-type voltage-gated calcium channels (VGCCs) at the soma and nucleus, although both NMDARs and IP3 receptors can also contribute to somatic and nuclear calcium signals under certain stimulation conditions (Nakamura et al. 1999; Bardo et al. 2006; Raymond and Redman 2006; Watanabe et al. 2006; Hong and Ross 2007; Hagenston et al. 2008; Bengtson et al. 2010). We review here the calcium signaling pathways underlying synaptically activated gene transcription leading to long-lasting changes in synaptic efficacy and memory as well as the physiological mechanisms by which synaptic activity evokes nuclear calcium signals.
Gesehen am 10.04.2018